Case Report: Spontaneous Appendicitis With Suspected Involvement of Klebsiella variicola in Two Pet Rabbits - Jekl, Vladimir; Piskovska, Anna; Drnkova, Ivana; Skoric, Misa; Hauptman, Karel; Chloupek, Jan (Frontiers in Veterinary Science, 2021)
Although laboratory rabbits are commonly used as models of appendicitis in man, spontaneous appendicitis was only described ante-mortem in one pet rabbit with an acute abdomen. The aim of this article is to describe two spontaneous cases of appendicitis in pet rabbits, to describe therapeutic appendectomy and to discuss the microbial flora of the inflamed appendix. A 5-month-old intact female and a 16-month-old, neutered male were presented to the veterinary clinic with restlessness, anorexia and reduced faecal output. The main clinical findings were restlessness, severe discomfort on abdominal palpation, a mid-abdominal palpable tubulous mass and an elevated rectal temperature. Blood analyses showed lymphocytosis, monocytosis and hyperglycaemia. Radiography was inconclusive. Abdominal ultrasound revealed a presence of tubular structure with wall thickness of 4.2 and 3.7 mm in the two rabbits respectively. The tubular structure had a rounded, closed end and a multi-layered wall, suggestive of appendicitis. Due to metabolic acidosis and poor prognosis, the first rabbit was euthanized. In the 16-month-old rabbit, appendectomy was performed. Recovery was uneventful and 4 hours after surgery, the rabbit started to become normally active. Postoperative care consisted of fluid therapy, multimodal analgesia, supportive care and prokinetics. Follow-up examinations at 10 days, 1 month and at 11 months after the surgery did not show any abnormal clinical or laboratory findings. Histopathological examination of appendices from both rabbits showed gangrenous appendicitis. Aerobic cultivation showed the presence of pure culture of Klebsiella variicola sensitive to enrofloxacin, marbofloxacin, tetracycline, cefuroxime, trimethoprim sulphonamide, neomycin, and gentamicin. Restlessness associated with anorexia, abdominal pain, palpable abdominal mass, hyperglycaemia, lymphocytosis, and elevated rectal temperature may be indicative of inflammation within the gastrointestinal tract. Abdominal ultrasound is recommended in rabbits with showing these clinical signs because radiography can be inconclusive. Appendicitis is a life-threatening condition, which should be included into the list of differential diagnoses for the rabbit an acute abdomen and gastrointestinal stasis syndrome and must be treated immediately. K. variicola may be associated with appendicitis in rabbits as a causative agent or in association with appendix intraluminal dysmicrobia.